Key factors regulating Plasmodium berghei sporozoite survival and transformation revealed by an automated visual assay - Hegge, Stephan; Kudryashev, Mikhail; Barniol, Luis Fernando; Frischknecht, Friedrich (The FASEB journal, 2010)
Malaria is transmitted to the host when Plasmodium sporozoites are injected by a mosquito vector. Sporozoites eventually enter hepatocytes, where they differentiate into liver-stage parasites. During the first hours after hepatocyte invasion, the crescent-shaped sporozoites transform into spherical intracellular exoerythrocytic parasites. This process, which precedes genome replication, can be mimicked in vitro in the absence of host cells. Here, we developed an automated method to follow transformation and cell death of sporozoites in vitro. This assay provides a rapid tool to test sporozoite survival and to screen for antiparasitic drugs. We found that extracellular bicarbonate and high temperature trigger transformation, whereas physiological serum albumin concentrations and media lacking bicarbonate delayed sporozoite death. Because bicarbonate also triggers ookinete transformation and exflagellation of gametocytes, we suggest that a common molecular mechanism regulates similar aspects of stage conversion in Plasmodium.—Hegge, S., Kudryashev, M., Barniol, L., Frischknecht, F. Key factors regulating Plasmodium berghei sporozoite survival and transformation revealed by an automated visual assay. FASEB J. 24, 5003-5012 (2010). www.fasebj.org